Joining strategy analysis of structural dynamic in top hat plate of dissimilar materials - N. A., Nazri; M. S. M., Sani; M. N., Abdul Rani; M. A., Yunus (2018)

(untitled)
Structural dynamic can be described as a study regarding analysis of model under exertion of dynamic loading. Joining in structure such as riveting, welding and soldering were strongly effects the structural dynamic properties. The aim of this paper is to conduct various joining strategy analysis in finite element software by using top hat plate structure in car as a model and result is compared with experimental data. Normal mode analysis with free-free boundary condition is applied. Resistance spot welding (RSW) technique is selected to weld flange part in top hat plate between dissimilar materials which is mild steel 1010 and stainless steel 304 with specified parameters applied. Modal testing via impact hammer test is carried out at the welded top hat plate for experimental analysis purpose. Correlation in between FEA and EMA results need to be conducted. By selecting identified parameters to execute model updating on the structure using sensitivity analysis method, the discrepancies in natural frequencies were reduced between FEA and EMA. CWELD element was chosen to represent weld model for spot weld joints due to its accurate prediction of frequencies and mode shapes compare to other weld modelling. As a closure, connection in structure parts play significant role in structural dynamics and model updating is one of successful method to lessen the discrepancies between FEA and EMA.